The Influence of Learning Styles, Self-Efficacy, Learning Facilities, and Parental Support on the Academic Achievement of Class X Students in Economics with Learning Discipline as a Moderating Variable - Fatima Azzahra; Desi Areva; Meri Rahmania (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the influence of learning styles, self-efficacy, learning facilities, and parental support on students’ learning achievement in Economics subject among tenth-grade students at SMA Negeri 10 Sijunjung, with learning discipline as a moderating variable. This research employed a quantitative approach with an associative method. The population consisted of 205 students, and a sample of 94 students was selected using stratified random sampling. Data were collected through a closed questionnaire, and the analysis was conducted using path analysis, t-test, and moderation analysis with the help of SPSS 22 and EViews 9 software. The results revealed that (1) learning style significantly influences learning achievement, (2) self-efficacy significantly influences learning achievement, (3) learning facilities significantly influence learning achievement, (4) parental support significantly influences learning achievement, (5) learning discipline significantly influences learning achievement, and (6) learning discipline moderates the relationship between learning style, self-efficacy, learning facilities, and parental support with learning achievement.